Implicit Teaching Strategies on Grammar Instruction: Students’ Prevailing Stance - Rizki Indra Guci; Nur Arifah Drajati (Aksara: Jurnal Bahasa dan Sastra, 2019)
Grammar teaching in foreign language education has been maintained by most theories as one thing playing a significant role in facilitating the process of learning to read, write, speak, and understand a foreign language. However, scholars label that role as controversial both in the research of second language acquisition (SLA) and language pedagogy. Thus, such condition results in a potential cause of confusion to teachers and students, then leads the researchers to a thoughtful theoretical debate on the topic of the way grammar should be taught: explicitly or implicitly. The aim of the present case study was to gain an insight into the prevailing stance of Indonesian English students on grammar teaching enrolled in a senior high school. To this end, a questionnaire, as well as interview sessions, were developed and validated based on one construct pair from SLA literature: explicit versus implicit instruction. The findings, in general, showed that the students were found to prefer implicit over explicit instruction. Nonetheless, the stance somewhat changed depending on the proficiency level of students. As an implication, this study supported Indonesian English students to maintain their stance on implicit teaching strategies on grammar instruction, regarding the help they can get in the process of natural acquisition of language. http://dx.doi.org/10.23960/aksara/v20i2.pp109-124